Anthropometry model generation based on ANSUR II database. (2016) - Zhou, Xianlian; Sun, Kay; Roos, Paulien E.; Li, Peng; Corner, Brian
This paper presents a three-dimensional (3D) anthropometry model generation (AMG) software framework based on the latest US Army Anthropometric Survey (ANSUR II) database. The software utilises principal component shapes derived from 3D body scans in the database and employs two complementary methods (feature analysis method and database method) to generate 3D surface models directly from anthropometric feature specifications. Virtual landmarks and 3D features identified on the surface models are the keys for success of the present approaches. It is demonstrated that the features calculated from these models are in good agreement with traditional tape or caliper measurements with a few exceptions due to measurement methodology or posture. Besides surface anthropometry, the software is able to construct a dynamic joint segment framework from any of the models and morph associated bones, muscles, interior organs, and clothing accordingly. This AMG software is a valuable tool for AMG in digital human/warfighter/patient modelling for various applications in biomechanics, human factors or ergonomics, physiology, and medicine.